Shooting sport in the context of military objects in the middle war period of Poland - Kocki, Wojciech; Przesmycka, Elżbieta (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
During the interwar period, sport played many special roles in Polish society at that time. In the unstable political and economic situation as well as during the first years of the interwar period when attempts were made to rebuild the Polish State after regaining independence through sport, it was possible to keep the society in increasingly better physical condition. This situation was conducive to strengthening citizens for a possible armed conflict. The Government’s limited budget and possibilities for financing the development of the army resulted in the formation of associations, clubs and paramilitary organizations that promoted the cultivation of physical agility. A few years after the end of World War I and the country’s increasingly better situation began to blur the boundaries between education and development of military physical culture and society through joint organizations and the possibility of using more common groups of people, especially shooting sports. Shooting as a sport was considered to be key in military terms. Already during the partitions, the partitioners built shooting ranges, which in the early interwar years were adapted to the needs of the country. Examples of shooting ranges from middle war period in Lublin were: Project of shooting range Kolejowego Przysposobienia Wojskowego named of Pułkownika Lisa-Kuli, Project of shooting range Związku Strzeleckiego in Dziesiąta disctrict, Project of shooting range of Lubelskiego Towarzystwa Łowieckiego near Dolnej Panny Marii street.